Reproductive Rights versus the Christian Culture of the Body: Two Different Perspectives - Machinek, Marian (Philosophy & canon law, 2019)
The comparison between the concept of sexual and reproductive rights and the idea of gender and the Christian culture of the body with its personalist anthropology reveals their essential differences. The concept of reproductive rights is permeated with individualism, where sex identity can be freely defined, and sexual activities of individuals—provided that they stay within the boundaries of law—are not subjected to any moral norms. The main point of the disagreement between the concept of reproductive rights and the Christian culture of the body concerns the meaning of human corporeality. For the former, human body is, in a certain way, an ‘outside’ of the self-determining subject. According to the latter view, human body participates in man’s dignity as his constituent dimension. Another difference revolves around the meaning of sexual activity. Efforts to force implementation of sexual and reproductive rights, along with gender informed law and culture, are dangerous to the fundamental group unit of society—the family—based on the marriage between man and woman.